Dietrich Bonhoeffer. 80 Years Since His Passing - Anatoliy Denysenko (Богословські роздуми: Східноєвропейський журнал богословʼя)
On 9 April 2025, Christian academia commemorated the 80th year since the death of the prominent German theologian and pastor Dietrich Bonhoeffer, who was executed by the Nazis a month before the end of World War II. Bonhoeffer left behind a great legacy as a minister of the church, as a patriot of his people, and as an author of theological works. Today, his theological contribution includes sixteen volumes of texts plus one volume of registers and appendices in German. Only the eighth volume of Widerstand und Ergebung, which contains letters and notes written by Bonhoeffer when he was already behind bars since April 1943, has been translated into Ukrainian. It was published under the title Sprotyv i pokora (eng. Resistance and Obedience). Any serious study of Bonhoeffer’s work that is being conducted in Ukraine today should be based on these primary sources. One of the main questions that Bonhoeffer raises in his work is: “Who can stand?” His answer is: not the one for whom reason, principles, conscience, personal freedom, and virtue are the highest authority, but the one who is ready to sacrifice all of this if he is convinced that by faith and through an exceptional connection with God he is “called to obedient and responsible action.” The life of such a responsible person is a response to the request and call of God. The only question is “where are these responsible people?” (wo sind die Verantwortlichen?).